2018
DOI: 10.1038/s41467-018-04387-2
|View full text |Cite
|
Sign up to set email alerts
|

Trait paranoia shapes inter-subject synchrony in brain activity during an ambiguous social narrative

Abstract: Individuals often interpret the same event in different ways. How do personality traits modulate brain activity evoked by a complex stimulus? Here we report results from a naturalistic paradigm designed to draw out both neural and behavioral variation along a specific dimension of interest, namely paranoia. Participants listen to a narrative during functional MRI describing an ambiguous social scenario, written such that some individuals would find it highly suspicious, while others less so. Using inter-subjec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(99 citation statements)
references
References 61 publications
9
90
0
Order By: Relevance
“…These fMRI studies and the results of the present study showed significant ISC in bilateral auditory cortices and language areas along the superior temporal cortex, parietal and midline areas, including precuneus, as well as frontal areas. The present results replicate earlier findings with complex natural stimuli, that is, consistent activation not only in primary sensory cortices but also in higher-order regions (Hasson et al, 2004;Lerner et al, 2011;Finn et al, 2018). Bilateral temporal areas are known to be involved in speech processing and comprehension (see e.g., Hickok and Poeppel, 2007), and therefore were expected to show ISC in our study.…”
Section: Interbrain Correlation During Listening To Speechsupporting
confidence: 92%
See 3 more Smart Citations
“…These fMRI studies and the results of the present study showed significant ISC in bilateral auditory cortices and language areas along the superior temporal cortex, parietal and midline areas, including precuneus, as well as frontal areas. The present results replicate earlier findings with complex natural stimuli, that is, consistent activation not only in primary sensory cortices but also in higher-order regions (Hasson et al, 2004;Lerner et al, 2011;Finn et al, 2018). Bilateral temporal areas are known to be involved in speech processing and comprehension (see e.g., Hickok and Poeppel, 2007), and therefore were expected to show ISC in our study.…”
Section: Interbrain Correlation During Listening To Speechsupporting
confidence: 92%
“…The ISC patterns we observed in typical readers were overall consistent with those previously found with fMRI during listening to natural speech (Wilson et al, 2008;Stephens et al, 2010;Lerner et al, 2011;Silbert et al, 2014;Finn et al, 2018). These fMRI studies and the results of the present study showed significant ISC in bilateral auditory cortices and language areas along the superior temporal cortex, parietal and midline areas, including precuneus, as well as frontal areas.…”
Section: Interbrain Correlation During Listening To Speechsupporting
confidence: 91%
See 2 more Smart Citations
“…For over a decade, inter-subject synchronization measures of brain activation have been well established in tasks related to auditory stimuli (Hejnar, Kiehl, & Calhoun, 2007), narrated stories (Finn, Corlett, Chen, Bandettini, & Constable, 2018) and movies (Glerean, Salmi, Lahnakoski, Jääskeläinen, & Sams, 2012;Hasson, Nir, Levy, Fuhrmann, & Malach, 2004;Kauppi, Jääskeläinen, Sams, & Tohka, 2010). These studies are based on earlier work demonstrating that brain regions produce similar temporal dynamics across participants experiencing the same task event concurrently (Hanson, Gagliardi, & Hanson, 2009).…”
Section: Introductionmentioning
confidence: 99%